2021
DOI: 10.31000/almaal.v2i2.3741
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Memengaruhi Wakif Dalam Berwakaf Online

Abstract: Wakaf merupakan salah satu filantropi Islam yang dapat menjadi alternatif sebagai pemerata kesejahteraan dan pengurang kemiskinan. Instrumen ini memiliki potensi yang cukup besar di Indonesia. Berdasarkan perhitungan yang dilakukan oleh Nasution (2005), wakaf uang memiliki potensi 3 triliun Rupiah per tahun. Namun, angka potensi tersebut belum teroptimalkan dengan baik. Dengan adanya era digitalisasi, beberapa nazhir memberikan fasilitas wakaf online untuk memaksimalkan potensi wakaf uang yang tersedia. Peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Digitalization has also influenced how people participate in zakat and waqf. A study by (Budiansyah and El Ayyubi, 2021) revealed that factors such as quality of information, service, trust, website quality, and promotion have a significant influence on encouraging waqif participation in online waqf. The digitalization of zakat and waqf has opened up new opportunities and challenged old traditions.…”
Section: Results and Discussion 1 "Digitalization Of Zakat And Waqf: ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Digitalization has also influenced how people participate in zakat and waqf. A study by (Budiansyah and El Ayyubi, 2021) revealed that factors such as quality of information, service, trust, website quality, and promotion have a significant influence on encouraging waqif participation in online waqf. The digitalization of zakat and waqf has opened up new opportunities and challenged old traditions.…”
Section: Results and Discussion 1 "Digitalization Of Zakat And Waqf: ...mentioning
confidence: 99%
“…Meanwhile, (Budiansyah et al, 2021) found that various factors, including the quality of information, service, trust, website quality, and promotion, influence waqif participation in online waqf. Therefore, digital platforms used for online waqf must pay attention to these factors to achieve maximum levels of participation.…”
Section: Results and Discussion 1 "Digitalization Of Zakat And Waqf: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of cash waqf digitalization is seen in four aspects: nazir, wakif, government, and religion (Mursyidah et al, 2022). The results of research (2021) show that the factors that influence wakif in waqf online are divided into five categories: service factors, information quality, trust, promotion, and website quality (Budiansyah & Ayyubi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wakaf merupakan salah satu bagian dari instrument filantropi islam yang dapat dimanfaatkan sebagai penunjang perekonomian (Budiansyah & Ayyubi, 2021). Menurut Hasanah (2018), wakaf berfungsi sebagai kegiatan sosial yaitu untuk pemerataan kesejahteraan dan pengentasan kemiskinan.…”
unclassified